Less-Crowded Tourism as Applied to Reviving Tourism Post-Covid-19 in Taram Village, Lima Puluh Kota Regency, West Sumatra through Asset-Based Community Development - Iis Ismawati; Nurul Fauzi; Ranti Komala Dewi; Andrik Marta; Ermiati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
The Covid-19 pandemic has had a significant impact on the tourism industry. The decrease in the number of visitors has affected the revenue of tourism operators and the economy of the village community, especially in the tourism sector of Taram Village. The Asset Based Community Development (ABCD) approach is used to rebuild the tourism sector in the new normal era by optimizing the potential of Taram Village's outstanding tourism resources. Community support results in diversifying tourist destinations by adding variations and increasing the number of attractions, such as corn-based educational tours targeting the school-aged market segment. These support efforts have also been able to enhance the local economy through the optimization of the added value of sweet corn, transformed into pilus and gelamai products, which are culinary specialties of Taram Tourism Village. Implementing the ABCK application serves as a medium for developing Taram Tourism Village, thus achieving sustainable and resilient tourism development in Taram.